From ‘play’ to political discourse: the propagandistic nature of stickers on Whatsapp (Revista Internacional de Folkcomunicação, 2021)
Stickers can be defined as sticker, label and sticker. Very similar to traditional gifs and emoticons, in digital conversations, stickers have suppressed the use of words and images. Because they are polysemic, they can be used in different situations of interaction, which gives a more fun tone to the subject to which they refer. This linguistic situation is what Discourse Analysis defines as a discursive slide. That is, through incursive and discursive ellipses there is a rupture in the linearity of the original discourse. In the case of politics, however, even if a new meaning is constructed, the propagandistic character of the stickers remains. Through exploratory and empirical research, the aim of this study is to understand the slippage of meaning in political discourses for stickers. For that, as the main theoretical-methodological support, the Discourse Analysis proposal developed by Patrick Charaudeau was used. In particular, through two modalities of construction and organization of discourse: the descriptive organization mode and the argumentative organization mode. In its linguistic components, the descriptive and the argumentative modes have the procedures of naming, qualifying, situating and locating the starting, passing and arriving assertions, which are important in our investigation and for the understanding of discursive slips and new meanings. produced. As a research corpus, four stickers published on Whatsapp in 2020 were chosen. The selection criterion was that of convenience, as there are no specific criteria that should be considered when choosing the sample. Discourse; persuasion; stickers; Whatsapp.